Depressive and Anxiety Symptoms of Healthcare Workers in Intensive Care Unit Under the COVID-19 Epidemic: An Online Cross-Sectional Study in China - Peng, Xiaofan; Meng, Xiangyu; Li, Li; Hu, Chenghuan; Liu, Wei; Liu, Zhiyong; Ma, Xinhua; Xu, Daomiao; Xing, Zhenhua; Zhu, Zhaowei; Liu, Bangshan; Zhang, Lina; et al. (Frontiers in Public Health, 2021)
Backgroud: Since the COVID-19 outbreak, intensive care unit(ICU) healthcare workers were responsible for the critical infected patients. However, few studies focused on the mental health of ICU healthcare workers. This study aimed to investigate psychological impact of COVID-19 on ICU healthcare workers in China. Methods: We distributed 9-item Patient Health Questionnaire (PHQ-9) and 7-item General Anxiety Disorder questionnaire (GAD-7) online to ICU healthcare workers in China. Respondents were divided into frontline and second-line according to whether contact COVID-19 patients. Depressive and anxiety symptoms of all respondents were evaluated based on their questionnaire scores. Results: 731 ICU healthcare workers were finally enrolled in our study, including 303 (41.5%) male, 383(52.4%) doctors and 617(84.4%) who aged 26-45 years. In all, 482(65.9%) ICU healthcare workers reported symptoms of depression, while 429(58.7%) reported anxiety. There was no significant difference between frontline(n=325) and second-line(n=406) in depression (P=0.15) and anxiety severity(P=0.56). Logistic regression analysis showed that being female, ICU work time>5 years, night duty number≥10 were risk factors of developing depressive and anxiety symptoms. Income reduction was separately identified as risk of anxiety. Additionally, ICU work time >5 years was also identified as risk of developing moderate-severe depressive and anxiety symptoms. Conclusions: Frontline ICU work was not associated with higher risk of depressive and anxiety symptoms during COVID-19 pandemic remission period in China. Actions like controlling night duty number, ensuring vacation, increasing income should be taken to relieve mental health problem. Furthermore, We should pay close attention to those who had worked long years in ICU.